Effect of obstructive cholestasis on sex axis in the adult male rats - E Nasiri (Babol University of Medical Sciences, 2003)
Background and Objective: Obstructive cholestasis is associated with overproduction of some materials such as endogenous opioids (EOP) and nitric oxide (NO) in the blood streams. Physiology of sex axis hormones could be affected by some of these changes. This study was done to investigate the relationship between obstructive cholestasis and sex axis in adult male rats. Methods: To study the topic, three groups of animals were used: No-surgery, sham-surgery, and surgical ligation of the bile duct. After 3 weeks, all animals were killed by ether. Serum concentration levels of inhibin B, FSH and LH were determined by ELISA and RIA, respectively. Findings: The level of inhibin B was significantly higher in cholestasis than control and sham, and serum FSH and LH were significantly higher in control and sham than cholestasis (P<0.05). Conclusion: The results showed that obstructive cholestasis decreased the levels of serum gonadotropins but in did not damage testicular functions.